Magnetic Field Structure in Molecular Clouds by Polarization Measurements. (5th March 2015) - Chen, W. P.; Su, B. H.; Eswaraiah, C.; Pandey, A. K.; Wang, C. W.; Lai, S. P.; Tamura, M.; Sato, S.
Abstract: We report on a program to delineate magnetic field structure inside molecular clouds by optical and infrared polarization observations. An ordered magnetic field inside a dense cloud may efficiently align the spinning dust grains to cause a detectable level of optical and near-infrared polarization of otherwise unpolarized background starlight due to dichroic extinction. The near-infrared polarization data were taken by SIRPOL mounted on IRSF in SAAO. Here we present the SIRPOL results in RCW 57, for which the magnetic field is oriented along the cloud filaments, and in Carina Nebula, for which no intrinsic polarization is detected in the turbulent environment. We further describe TRIPOL, a compact and efficient polarimer to acquire polarized images simultaneously at g', r', and i' bands, which is recently developed at Nagoya University for adaption to small-aperture telescopes. We show how optical observations probe the translucent outer parts of a cloud, and when combining with infrared observations probing the dense parts, and with millimeter and submillimeter observations to sutdy the central embedded protostar, if there is one, would yield the magnetic field structure on different length scales in the star-formation process.